RANCANG BANGUN APLIKASI RAPOR BERBASIS ANDROID (Studi Kasus : SMA Negeri 1 Rengat Barat) - Dhandy Syahputra; Zulhendra Zulhendra (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
SMA Negeri 1 Rengat Barat still uses the manual method in processing student grade data for the 2013 curriculum by collecting grades data from each subject teacher managed by the homeroom teacher. The programming language uses PHP (Pear Hypertext Processor) and the database design uses MySql. The results of the report card application design at SMA Negeri 1 Rengat Barat is a system that provides information to each homeroom teacher when they want to input data on the value of learning activities and students can directly see the value of the report card results of teaching and learning activities when all homeroom teachers have input each result. Mark. The information presented in this system includes information that the homeroom teacher can directly input the value of the results of teaching and learning activities in the form of report cards so that students can directly see the report cards of teaching and learning outcomes directly. The design of this report card application is very important as a support in recording the data processing of the 2013 curriculum based on android students.